Factors associated with neck pain in high school students of a state educational institution, Lima – Peru - Santiago Bazan, Cristhian (2019)
Objective: To determine the factors associated with neck pain in students of a state educational institution in Lima, Peru. Materials and methods: A descriptive, cross-sectional and correlational study was conducted with 300 high school students. A questionnaire consisting of 19 questions and validated by 11 experts was prepared. Each item was evaluated (sufficiency, clarity, coherence and significance) using the Aiken’s V statistic (0.91). The reliability of the instrument was determined with Cronbach's alpha (0.826), which indicated a high level of reliability of the instrument regarding the association among categorical variables. A chi-square test was used to establish the significant differences (p<0.05). Results: A statistically significant relationship was found between cervical pain and factors such as age (p = 0.001) and educational status (p = 0.001). Conclusions: Neck pain is a public health problem. It does not necessarily occur in adulthood but also at early ages, which has been demonstrated in the present research. If not treated on time, it would lead to a functional limitation affecting the quality of life.